Radiofrequency applicator concepts for simultaneous MR imaging and hyperthermia treatment of glioblastoma multiforme - Oberacker Eva; Kuehne Andre; Nadobny Jacek; Zschaeck Sebastian; Weihrauch Mirko; Waiczies Helmar; Ghadjar Pirus; Wust Peter; Niendorf Thoralf; Winter Lukas (Current Directions in Biomedical Engineering, 2017)
Glioblastoma multiforme is the most frequent and most aggressive malignant brain tumor with de facto no long term curation by the use of current multimodal therapeutic approaches. The efficacy of brachytherapy and enhancing interstitial hyperthermia has been demonstrated. RF heating at ultrahigh fields (B0=7.0T, f=298MHz) has the potential of delivering sufficiently large thermal dosage for hyperthermia of relatively large tumor areas. This work focuses on electromagnetic field (EMF) simulations and provides realistic applicator designs tailored for simultaneous RF heating and MRI. Our simulations took advantage of target volumes derived from patient data, and our preliminary results suggest that RF power can be focused to both a small tumor area and a large clinical target volume.